Effect of polydopamine (PDA) coating on the mechanical, thermal, and morphological properties of recycled polylactic acid (rPLA)/kenaf fiber (KF) composites in Fused Deposition Modeling (FDM) - Hamat, Sanusi; Ishak, Mohamad Ridzwan; Salit, Mohd Sapuan; Yidris, Noorfaizal; Showkat Ali, Syamir Alihan; Hussin, Mohd Sabri (Elsevier Editora Ltda, 2025)
This study examines the impact of self-polymerized polydopamine (PDA) coating on the mechanical, rheological, and microstructural properties of recycled polylactic acid (rPLA)/kenaf fiber (KF) composites fabricated via Fused Deposition Modeling (FDM). Biodegradable filaments were produced by reinforcing rPLA with 5–20 wt% bast kenaf fibers and coating them with dopamine prior to melt compounding. Mechanical tests (tensile, flexural, and compression) revealed that PDA treatment substantially enhances fiber–matrix adhesion, leading to significant improvements in tensile yield stress (up to 21.92 MPa) and ultimate tensile strength (44.5 MPa), far exceeding uncoated rPLA (14.42 MPa and 18.6 MPa, respectively). Flexural strength peaked at 54.7 MPa for the 5 wt% composite, while 20 wt% kenaf markedly boosted compression strength to 65.4 MPa roughly 74 % above neat rPLA. Rheological measurements indicated that moderate fiber loadings (≤10 wt%) and PDA coating stabilize melt flow, minimizing clogging risks and supporting uniform extrusion. By contrast, higher fiber contents induced particle agglomeration and viscous instabilities, complicating FDM processability. Microscopic analyses verified that PDA-mediated bonding reduces crack propagation, despite increased porosity from higher kenaf additions. Overall, this bioinspired surface modification strategy yields sustainable rPLA-based composites with notably enhanced mechanical and favorable rheological behavior, highlighting promising applications in 3D printing and related industries.